Influence of inhibition of return on different components of action in two visually guided motor tasks - Huertas, F.; Castellote, J. M.; Lupianez, J.; Sanchez-Alarcos, J. V.; Sanegre, M. T. (International Journal of Computer Science in Sport, 2002)
Human action in reaction time tasks is highly dependent on perception. In motor tasks, such as sports that demand high accuracy for hand grasping, adequate processing of visual information is critical. Visual attention maximizes searching of relevant stimuli to optimise human response.In studies of exogenous attentional orientating with variable delays between cue and target (Stimulus Onset Asynchrony or SOA), response time for targets at previously cued locations is longer than for targets at uncued locations, mainly at long SOAs. The effect, known as Inhibition of Return (IOR), has been observed in discrimination as well as detection tasks (Lupianez et al., 1999; Klein, 2000). We explored how IOR mediates action in two visuallly guided motor tasks.